Improved design and test of flexible cotton stalks puller - Cai, Jialin; Zhang, Jiaxi; Guo, Gang; Gao, Zebin; Wang, Xiaoxuan (International Journal of Agricultural and Biological Engineering, 2023)
In Xinjiang, in the process of whole stalk harvesting of cotton stalks, there is a problem that the cotton stalks are easily pulled off, and there is an urgent need to develop flexible stalk-pulling machines. Through literature, patent summary, and field research, it is found that domestic researchers have designed many kinds of machines for the problem of easy breaking of cotton stalks, but there is no flexible cotton stalk-pulling machine for the time being. In this study, two flexible cotton stalk-pulling machines were intended to address the problem of easy breakage of cotton stalks. On the basis of the first-generation machine, the design of the second-generation machine was improved. In order to further improve the operational performance of the flexible cotton stalks pulling tools, the operational mechanism of the core working parts of the tools was analyzed and a comparative test was done in a large field. Analysis and the comparative tests proved that improving the clamping working stroke s of the stalk-pulling components can effectively reduce the cotton stalks leakage rate. By using a flexible clamping process, a part of the deformation of cotton stalks can be transferred to the flexible material. To a certain extent, the deformation length L of the contact surface between the cotton stalk and the stalk pulling part is reduced, and the deformation displacement Δy is correspondingly lower. The toughness of the cotton stalk is not significantly decreased and the cotton stalk does not break easily. The improved second-generation machine has a 3.67% to 3.79% lower cotton stalks leakage rate and a 5.65% to 6.30% lower cotton stalks breakage rate than the first-generation machine. As the land in Xinjiang is clay soil, soil bonding to cotton stalks pulling force F2 is larger, resulting in cotton stalks being more difficult to be pulled out of the machine at once. The test proved that the improved second-generation implements had a significant improvement in the cotton stalk-pulling effect because of the subsequent pulling interval CD. The test results verify the analysis results and the research results can provide a theoretical basis for the subsequent structural improvement and performance enhancement of the flexible cotton stalk-pulling machine, which is of reference significance for solving the problem that the cotton stalks are easily pulled and broken in Xinjiang, China. Keywords: agricultural machinery, flexible material, optimized design, verification test, cotton stalks puller DOI: 10.25165/j.ijabe.20231603.7267 Citation: Cai J L, Zhang J X, Guo G, Gao Z B, Wang X X. Improved design and test of flexible cotton stalks puller. Int J Agric & Biol Eng, 2023; 16(3): 78–84.